New bioactive triaryl triglyceride esters: Synthesis, characterization and biological activities (Bangladesh Journal of Pharmacology, 2018)
Four new bioactive aryl triester derivatives of glycerol and benzoic acids were synthesized. The synthetic compounds were studied for their antimicrobial and urease inhibition activities. Esterification was carried out by using carbonyldiimidazole to enhance the acyl elimination addition reaction with benzoic acid derivatives. The structure of triglycerides were studied by EI-MS, 1H, 13C-NMR, FT-IR and elemental analysis. All synthetic compounds showed urease inhibition activity with highest value of IC50 value 22.4 ± 0.45 μM which is nearest to standard thiourea IC50 value (21.6 ± 0.12 μM).  Except compound (3d), all other compounds exhibited antimicrobial activity against Streptococcus pneumoniae, Staphylococcus epidermidis, Bacillus pumilus, Escherichia coli, Pseudomonas aeruginosa and Candida albican.Video Clip of Methodology:7 min 59 sec   Click to watch